1996
DOI: 10.1007/bf00014990
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the biology of the rare Branchipus visnyai Kertesz 1956 (Crustacea, Anostraca) from Monti Reatini (Latim, central Italy)

Abstract: Branchipus visnyai is presently known from only one location, in Italy, on Monte Catabio (central Appennine, Latium, 1590 m a.s .l) . It lives in a large astatic pond and in a small temporary pool close to the pond . Typically two generations appear in the pond (in spring after snowmelt and in autumn after dilution by rainfall), unless an exceptionally dry season occurs . Yet, due to shallowness and small size, filling and duration of the pool is erratic and depends on the annual amount of snow and rainfall . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…where permanent surface water is scarce and aquatic life is mainly supported by small lakes and permanent ponds. Accordingly, it is also known that these precious water bodies show distinctive communities including nationally rare species (Stella 1988, Mura 1993, Cianficconi et al 1994, Mura 1996, Di Giorgio & Zuppa 1996, Mura et al, 2003. Due to their limited dimensions they are particularly sensitive to weather changes and environmental modifications.…”
Section: Introductionmentioning
confidence: 99%
“…where permanent surface water is scarce and aquatic life is mainly supported by small lakes and permanent ponds. Accordingly, it is also known that these precious water bodies show distinctive communities including nationally rare species (Stella 1988, Mura 1993, Cianficconi et al 1994, Mura 1996, Di Giorgio & Zuppa 1996, Mura et al, 2003. Due to their limited dimensions they are particularly sensitive to weather changes and environmental modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Differences were, in fact, noted by Mura (1996) in hatching requirements in particular, in a field study concerning the population previously considered by Cottarelli, and another one living in a small pool nearby; unfortunately, however, at that time they were considered distinct species, and morphological investigation was not within the scope of the study. …”
Section: Results Discussionmentioning
confidence: 98%
“…Since 1969, when Cottarelli raised to the species level what Kertész (1956) had considered a variety of Branchipus schaefferi on the basis of differences observed in the shape of the frontal shield and the degree of flexure of the furcal rami and of distal articles of antennae in males (Kertész, 1956;Cottarelli, 1969), B. visnyai was regarded as a valid species (Cottarelli & Mura, 1983;Lanfranco et al, 1991;Mura, 1996Mura, , 1999. As previously outlined by Brtek (1962) in the populations from Czechoslovakia, a detailed morphological study on a number of B. schaefferi populations from the Pannonian Plain (Marincek & Petrov, 1988, Abstract in Zbornik radova o fauni Srbije, SANU, p. 5) revealed a great variation in such characters.…”
Section: Introductionmentioning
confidence: 99%
“…This medium had to be diluted by more than 50% before hatching of S. torvicornis took place. Moreover, the medium from both species, which frequently coexist (Thiéry, 1991(Thiéry, , 1996Petrov and Cvetkovic, 1997;Mura and Cottarelli, 1998;Beladjal et al, 2003), has a strong inhibitory effect on the hatching of each others' resting eggs, but this effect was very weak when medium from a non-coexisting species, C. diaphanous (a cold adapted species) was used. Even in locations where resting eggs of the three different species are found together, the reproductive season of C. diaphanus alternates with that of S. torvicornis and B. schaefferi; thus, the former does not coexist as an adult with the latter two species.…”
Section: Discussionmentioning
confidence: 98%
“…Although nauplii are rarely found in pools with conspecific adults, Hall (1961) and Mura (1995Mura ( , 1996 observed a second generation of Chirocephalus and Branchipus after an initial decrease in the pond level, followed by refilling. Hall suggested that "some factor may inhibit or retard development", presumably being diluted to allow for resting egg hatching and the second generation.…”
Section: Introductionmentioning
confidence: 96%